Transforming Pedagogical Practices through Deep Learning in Elementary Education - Ahmad Salim; Agus Tinus; Kuncahyono Kuncahyono (AL-ISHLAH: Jurnal Pendidikan, 2026)
Despite growing interest in deep learning pedagogy as a means of fostering meaningful and student-centered learning, limited empirical research has examined how pedagogical practices are reshaped through its implementation in authentic elementary school classrooms, particularly within the Indonesian context. This study investigated how deep learning pedagogy was perceived to support changes in teaching practices and meaningful learning experiences in an international elementary school setting. A single-site qualitative case study was conducted at Fatimah International Elementary School, Indonesia, involving 13 participants consisting of three teachers, nine students, and one academic coordinator. Data were collected through classroom observations, semi-structured interviews, and document analysis and were analyzed using thematic analysis. The findings suggest that deep learning pedagogy supported a shift from transmission-oriented teaching toward more student-centered, reflective, and collaborative classroom practices. Meaningful learning emerged when instructional activities were connected to students’ everyday experiences and supported through inquiry, discussion, and authentic learning tasks. Reflective learning practices appeared to strengthen learner agency, metacognitive awareness, and self-regulated learning, while collaborative activities enhanced students’ cognitive, emotional, and social engagement. However, implementation required careful instructional preparation, classroom management, and institutional support. These findings contribute to the growing discourse on deep learning pedagogy by providing contextual evidence from elementary education and highlighting its potential to foster meaningful learning environments. The study suggests that teachers and school leaders should promote reflective, collaborative, and contextually relevant learning experiences while ensuring adequate pedagogical and organizational support for sustainable implementation.